Transparently interposing user code at the system interface - Jones, Michael B. (School of Computer Science, Carnegie Mellon Univ., 1992)
Abstract: "Many contemporary operating systems utilize a system call interface between the operating system and its clients. Increasing numbers of systems are providing low-level mechanisms for intercepting and handling system calls in user code. Nonetheless, they typically provide no higher-level tools or abstractions for effectively utilizing these mechanisms. Using them has typically required reimplementation of a substantial portion of the system interface from scratch, making the use of such facilities unwieldy at best
Zugl.: Pittsburgh, Pa., Univ., Diss., 1992
Keywords: Operating systems (Computers); Schnittstelle; Betriebssystem; Hochschulschrift